Best Practices in Historical Studies of Nursing and Health (1999-2017) - Amanda Nicácio Vieira; Stéfany Petry; Maria Itayra Padilha
ABSTRACT Objective: to analyze the best practices thematic in dissertations and theses produced by a research group of history of nursing and health from 1999 to 2017. Method: a documentary socio-historical research with a qualitative approach. Documentary sources were dissertations and theses using content analysis. Results: 30 dissertations and 20 theses were found with compliance with the objective. Best practices refer to care and assistance practices, the history of institutions and organizational entities, and the implementation of nursing practices in each institution. Educational process addresses best practices in support groups, educational institutions and specialty construction. Other studies bring the milestones of the nursing profession, confrontation situations and social reflection regarding vulnerabilities. Final considerations: the studies address best practices in nursing that go through several settings in the attempt to raise problems and promote scientific research to support nursing actions in care.